Gender implications of agricultural commercialization in Africa: Evidence from farm households in Ethiopia and Nigeria - Berhane, Guush; Abay, Mehari Hiluf; Seymour, Greg (International Food Policy Research Institute, 2022)
Agricultural commercialization is often pursued as an important driver of agricultural transformation in low-income countries. However, the implications it can have on gendered outcomes are less understood. While agricultural commercialization creates opportunities to increase income, this may come at the expense of change in women’s decision-making agency and control over resources. Understanding the interactions between agricultural commercialization and gender outcomes is thus critical for policymakers aspiring to achieve agricultural transformation while promoting gender equity and the evidence on the links between the two in the context of Africa is scarce and mixed. We use three rounds of Ethiopia’s and Nigeria’s LSMS-ISA panel data to understand the implications of agricultural commercialization to gendered decision-making on crop harvest use, marketing, revenue control, asset ownership, and intrahousehold budget allocation. Results indicate commercialization is associated with decreases in women’s participation in decision-making related to use of harvest, crop marketing, and control over revenue in Ethiopia, but only on harvest use and control over revenue in Nigeria. The association with land ownership is mixed: positive in Ethiopia but negative in Nigeria. Moreover, commercialization is associated with decreases in women’s share of farm-workload but with increases in share of hired labor in Ethiopia. In Ethiopia we also find women’s control over revenue is positively associated with increases in per capita consumption expenditures and dietary diversity, but men’s control is negatively associated with increases in the share of expenditure on children’s shoes and clothes. In Nigeria, women’s control is positively associated with increases in the share of expenditure on women’s shoes and clothes, food gap, and dietary diversity. In sum, we find suggestive evidence that commercialization may further marginalize women’s decision-making agency in Ethiopia and Nigeria. However, conditional on women’s control over proceeds, commercialization tends to improve women’s as well as other members’ welfare. We provide some policy recommendations and directions for future research.